Effects of Cinnamomum camphora coppice planting on soil fertility, microbial community structure and enzyme activity in subtropical China - Sun, Luyuan; Zhang, Jie; Zhao, Jiao; Lu, Xianghui; Xiao, Changlong; Xiao, Zufei; Zhang, Ting; Gu, Yueqi; Sun, He; Liu, Han; Li, Yanli (Frontiers in Microbiology, 2023)
Cinnamomum camphora (C. camphora) is a broad-leaved evergreen tree cultivated in subtropical China. Currently, the use of C. camphora clonal cuttings for coppice management has become popular. However, the effects of C. camphora coppice planting on soil abiotic and biotic variances remained unclear. In this study, we collected soil from three points in the seven-year C. camphora coppice planting land: under the tree canopy (P15), between trees (P50), and abandoned land (Control) to investigate the effects of C. camphora coppice planting on soil fertility, microbial community structure and enzyme activity. The results revealed that C. camphora coppice planting significantly increased soil fertility in the point under the tree canopy (P15) and point between trees (P50), and P15 had more significant effects than P50. Meanwhile, in P15 and P50, soil bacterial, fungal alpha-diversity were improved and microbial community structures were also changed. And the changes of soil organic carbon (SOC) and total nitrogen (AN) promote the transformation of soil bacterial, fungal community structures, respectively. In addition, C. camphora coppice planting significantly increased soil urease (UE), polyphenol oxidase (PPO), and peroxidase (POD) activities, while significantly decreased soil ACP activity. This study demonstrated that the C. camphora coppice planting could improve soil fertility in subtropical China, which promoted the transformation of soil microbial community from oligotrophs (K-strategist) to copiotrophs (r-strategist). Thus, this work can provide a theoretical basis for soil sustainable utilization and productive management of C. camphora coppice plantation in subtropical China.